W-Band Vector Millimeter Wave Signal Generation Based on Intensity Modulators Without DAC - Yitong Li; Jianguo Yu; Naibo Zhang; Kun Deng; Guangyao Yang; Ruiliang Song (IEEE Photonics Journal)
We proposed and experimentally demonstrated a novel method to generate an adaptive N2-quadrature amplitude modulation (N2-QAM) W-band vector millimeter wave (mm-wave) signal based on intensity modulators without digital to analog converter (DAC). Two N-amplitude shift keying (N-ASK) signals are synthesized into N2-QAM W-band mm-wave vector signals by employing two Mach-Zehnder modulators, paralleling phase shifters, attenuators and a single optical mixer. In this scheme, DAC and additional digital signal processing are omitted at the transmitter, and double bit rate can be obtained at the user end. Taking the case of N = 2 as an example, we finally used 2-ASK signals to generate 80-GHz 4-QAM W-band mm-wave, and completed its high-performance transmission over a 1-m wireless link. The measured bit error rate (BER) performance can reach below 7% hard-decision forward-error-correction (HD-FEC) threshold of 3.8 × 10−3.